Archie Weller's Land of the Golden Clouds: Science Fiction Novel as Allegory of Multiculturalism - Polak, Iva (2003)
When unwrapped from the genre of science fiction, Archie Weller’ s latest novel Land of the Golden Clouds, reveals a story that touches upon the issues no longer detached from the present Australian (and global) yearning. What is unveiled is not just the story of a group of people belonging to different tribes on the quest to defeat the archetypal evil, but a story of different and shifting identities trying to find a common language in order to remap the landscape. As such, the novel surpasses the boundaries of science fiction and penetrates into the present day Australian/global context marked (sometimes even marred) by antinomies of globalism and localism, nationalism and ethnicity, monoculture and multiculturality.
Projekt MZOS
ENG